Evaluation of Students of Islamic Countries of the Faculty of Sharia and the Islamic Cultural Center at the University of Jordan for their Role in Establishing Shari’a Sciences and Intellectual Security - Awaysheh , Ahmed (Dirasat: Shari’a and Law Sciences, 2020)
This study aims at identifying the role of the Faculty of Shari’a and the Islamic Cultural Center at the University of Jordan in establishing the Islamic science and achieving intellectual security for international students from their point of view. The sample of the study consisted of (119) international students, randomly selected, and of different nationalities. The study used the descriptive method to describe the research terms and clarify the study’s determinants and provide an overview of the efforts of both the Faculty of Sharia and the Islamic Cultural Center for their role toward students of Islamic peoples and the inductive method by extrapolating the opinions of students from Islamic peoples in the Faculty of Sharia and the Islamic Cultural Center in the most important results derived from them. The study reveals a positive outcome in the evaluation concerning the attitudes of international students towards the role of the Faculty of Shari’a and the Islamic Cultural Center at the University of Jordan in both sections of the questionnaire. There are no statistically significant differences at (0.05≥α) according to the study variables (gender, specialization, school year).